Mechanisms by which Human Cells Bypass Damaged Bases during DNA Replication after Ultraviolet Irradiation - James E. Cleaver (The Scientific World Journal)
The replication of damaged DNA involves cascading mechanisms of increasing complexity but decreasing accuracy. The most accurate mechanism uses low-fidelity DNA polymerases, Pol H and Pol I, which have active sites sufficiently large to accommodate a pyrimidine dimer. Replicative bypass of DNA damage by these polymerases produces an accurately replicated, newly synthesized strand. Pol H negative cells (XP-V cell lines) either adopt a proposed secondary bypass mechanism or a recombinational mode. The mechanism of the secondary bypass is unclear, but a number of experiments suggests roles for excision repair to remove damage ahead of replication forks, hRad6/18 proteolysis to clear the blocked forks, and the Rad17-RFC and 9-1-1 complexes to establish a new replication apparatus. This alternative pathway requires functional p53. In Pol H negative cells in which p53 is also inactive, the arrested fork fragments into DNA double strand breaks. Foci containing PCNA, Mre11/Rad50/Nbs1, and gamma-H2Ax can then be detected, along with chromosomal rearrangement and high frequencies of sister chromatid exchanges. The recruitment of recombination components to the arrested forks represents the ultimate failure of replication machinery to relieve the arrested state and bypass the damage. The resulting chromosomal instability in surviving cells will contribute to malignant transformation.